Barriers to reporting of medication administration error among nurses working in a teaching hospital, Kathmandu. - Shrestha,Sapana (2018)
ABSTRACT: Medication administration error reporting has been accepted as a basic attempt for the improvement of patient safety. The main objective of the study is to identify the barriers to reporting of the medication administration error among nurses. Descriptive cross sectional research design was used. All the registered nurses working on various inpatient units of Tribhuvan University Teaching Hospitals, Maharajgunj , Kathmandu were taken as study population . Proportionate stratified random sampling technique was used to select 228 nurses. A structured questionnaire was used to collect data. The findings were entered into EPI DATA 3.1 and transferred onto the statistical package for social science 16 version for further analysis. Data was analyzed and interpreted by descriptive; mean, median, standard, frequency and percentages and inferential statistic; independent t test, one way ANOVA. Possible medication administration error was wrong dose (66.7.%). Fear (1.76_+0.36) and administrative response (1.46_+0.39) related barrier was major barrier to reporting of medication administration error among nurses. It is observed that nurses who had less than five years of work experience present higher perception level regarding administrative response barriers in reporting MAEs. there is significant difference between disagreement over error related barrier and background variables such as age (p=.02,marital status (p=.01), work experience (0.006). In , conclusion, fear and administrative response related barrier is present as most influential barrier to reporting of Medication Administration Error. Fear of being blame, fear of incompetency, fear of termination of job, fear of being legally sued were major barrier perceived by nurses. So it is necessary to establish communicative environment in inpatient unit to reduce fear and provide positive reinforcement to encourage reporting. Key Words: Barrier, Medication administration error, Reporting